Comparison of waste plastics pyrolysis under nitrogen and carbon dioxide atmospheres: a thermogravimetric and kinetic study - Md Saad, Juniza; Williams, Paul T.; Zhang, Ye Shui; Yao, Dingding; Yang, Haiping; Zhou, Hui (Elsevier, 2021)
It is important to understand the influence of pyrolysis atmosphere on the thermal degradation of waste plastics. In this study, the decomposition of waste plastics; high and low density polyethylene, polypropylene, polystyrene, and polyethylene terephthalate were investigated from ambient temperature to 500 °C within nitrogen or carbon dioxide atmospheres. The thermal degradation characteristics and kinetic parameters of individual plastics and mixed plastics (household packaging, building construction and agricultural waste plastics) from three different waste treatment plants were investigated under N2, CO2 and N2/CO2 atmospheres. In all atmospheres, only one degradation peak temperature was observed between 250−510 °C. The replacement of N2 by CO2 showed different effects on the activation energy. Mixtures of N2/CO2 in the pyrolysis atmosphere resulted to lower activation energy for all plastic samples, with the exception of high density polyethylene, polystyrene and polyethylene terephthalate. The lower activation energy suggested that lower energy was required for the degradation process. However, a mixture of more than 30 % of CO2 may influence the degradation process of plastics due to a higher value of residue obtained after the experiment.